PENGGUNAAN MEDIA PEMBELAJARAN OLEH GURU SEKOLAH DASAR SEBAGAI PENUNJANG KEGIATAN BELAJAR MENGAJAR - Lestari, Sudarsri (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2016)
Each of teachers andpractitioners should have to be ableto develop a learning tool. Instructional media is part of a learningtool. The purpose of this study is to determine: (1) the ability ofprimary school teachers in the use of instructional media; (2) theexperience of primary school teachers in the use of instructionalmedia; and (3)the problems faced by teachers in the use ofinstructional media. This study used a qualitative approach withcase study. The results showed that: (1) not all teachers are ableand willing to make learning media to support any teaching andlearning activities; (2) at the time of using instructional media,students be more enthusiastic and interested to participate inlearning, but teachers are reluctant to use instructional media inthe teaching and learning process; and (3) to teach usinginstructional media, teachers feel it is rather difficult to use mediafor classroom management.